2009
DOI: 10.1159/000235687
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Is a Predictor of Mortality in Stable Hemodialysis Patients

Abstract: Background/Aims: Mortality in end-stage renal disease patients with dialysis remains high. A high percentage of dialysis patients display signs of chronic microinflammation. To clarify whether microinflammation is involved in the high incidence of poor prognosis in dialysis patients, we investigated the association of inflammatory markers with mortality in a prospective observational cohort study. Methods: 120 patients undergoing hemodialysis were enrolled. Baseline cross-sectional analysis of the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 55 publications
2
32
0
2
Order By: Relevance
“…Since IL-6 is accepted as a negative predictive factor for mortality in HD patients [1,3], it is possible that in stable HD patients a mild degree of acidosis is in fact a positive marker as stated by large cohort studies [11,19]. This is supported by our data which showed a better nutritional state in the patients with acidosis, as reflected by a higher protein catabolic rate and transferrin.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Since IL-6 is accepted as a negative predictive factor for mortality in HD patients [1,3], it is possible that in stable HD patients a mild degree of acidosis is in fact a positive marker as stated by large cohort studies [11,19]. This is supported by our data which showed a better nutritional state in the patients with acidosis, as reflected by a higher protein catabolic rate and transferrin.…”
Section: Discussionsupporting
confidence: 80%
“…The proinflammatory interleukin-6 (IL-6) increases during HD and has been associated with cardiovascular mortality, malnutrition and resistance to erythropoietin (EPO) in HD patients [1,2]. IL-6 is considered a prognostic marker among these patients [3]. IL-10 is an anti-inflammatory cytokine, operating as a counterregulatory mediator.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of chronic hemodialysis (HD) patients have elevated serum levels of inflammatory markers (1,2) that are powerful predictors of mortality in this population (2)(3)(4)(5)(6)(7). A generalized increase in the inflammatory response in patients with ESRD may occur via decreased clearance of proinflammatory cytokines, volume overload, oxidative and carbonyl stress, patient-related mechanisms (underlying disease and comorbidities), as well as factors related to dialysis technique.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms of possible causes of inflammation in ESRD patients are discussed elsewhere (8 -10). Among the various cytokines, IL-6 was found to be most closely related to mortality (3,4,6,7) and to be associated with more causes of inflammation than other cytokines and Creactive protein (CRP) (11,12). While an experimental study by Ling et al (13) suggested that protein-energy wasting (PEW) produces changes in inflammationrelated protein characteristics of a low-grade systemic inflammatory response, clinical studies (14 -16) found inflammation, PEW, and cardiovascular morbidity to be interrelated in HD patients, each additionally contributing to the high mortality in HD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Second, study participants underwent coronary angiography, and so they may not be representative of all dialysis patients. Third, we did not measure other biomarkers associated with mortality and cardiovascular events in dialysis patients, such as levels of interleukin 6, fibroblast growth factor 23, homocysteine and soluble isoform of Flt-1 [34,35,36,37,38], although the HRs of adverse events for PlGF were not attenuated after adjustment for BNP and CRP levels.…”
Section: Discussionmentioning
confidence: 99%